Hubungan antara Gaya dan Iklim Belajar terhadap Minat Siswa pada Pelajaran Agama Buddha SMA di Kalimantan Tengah - Ariani Ariani (Dhammavicaya : Jurnal Pengkajian Dhamma, 2024)
Students' learning interest in Buddhist Education subjects in Central Kalimantan tends to be low, indicated by the lack of active participation, attention and discipline of students during the learning process. This study aims to empirically examine the relationship between learning styles (X1), learning climate (X2) and simultaneously to learning interest (Y). The research subjects were high school Buddhist students in Central Kalimantan with a sample size of 52 students. This study uses a correlational quantitative approach. Data were collected using a questionnaire with a Likert scale. Data analysis techniques with descriptive statistics, validity tests, reliability, basic and classical assumption tests followed by hypothesis testing with correlation, coefficient of determination and partial hypothesis with t test. The results of partial hypothesis testing with t test with the first hypothesis at a significance level of 0.05 obtained a value of 0.501 which is greater than 0.05 means reject Ho and there is no positive relationship between learning style (X1) and interest in learning (Y). The second hypothesis at the 0.05 significance level obtained a value of 0.000 which is smaller than 0.05 which means accept Ho and there is a positive relationship between learning climate (X1) and interest in learning (Y). The third hypothesis obtained F count (32.606) > F Table (3.19) so accept Ha which means there is a positive relationship between learning styles (X1) and learning climate (X2) together on interest in learning (Y).